Designing powerful professional development for teachers and principals - Sparks, Dennis (National Staff Development Council, 2002)
Dennis Sparks' book is both insightful and easy to read. It is a well-researched, practical guide to staff development at all levels of the educational system. It is grounded in three fundamental principles: "quality teaching makes a difference in student learning, professional learning of teachers and principals is a central factor in determining the quality of teaching, and third, district structures and culture that surround the school play a critical role in determining the quality of professional learning"